Financial Performance Analysis of PT A Based on Liquidity Ratio - Dithisari, Indri; Hartika, Lia (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
The research objective is to determine the financial performance of PT A from 2018 to 2022 in terms of the liquidity ratio. The type of data used in writing this final project report is quantitative data using secondary data, namely the financial position report from 2018 to 2022. The results of this study indicate that the financial performance of PT A is said to be in bad financial condition because the average liquidity ratio results are below industry standards. It can be concluded that PT A is an illiquid company and has an unfavorable financial condition.